2010
DOI: 10.1007/s11062-010-9138-4
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Spike Activity in Micropopulations of Motor Cortex Neurons in Rats

Abstract: Using eight-channel metal microelectrodes (diameter of a separate channel 12 µm), we extracellularly recorded the impulse activity of 186 single neurons or their small groups (usually, pairs) localized in the motor cortex of rats anesthetized with ketamine. In 60 cases (32.3%), action potentials (APs) of two single neurons were generated in a parallel manner and demonstrated fixed time relations with each other. This is interpreted as being a result of excitation of two neighboring functionally connected (coup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Thus, a structural scheme of the method for the objective diagnosis of respiratory and olfactory disturbances was developed, taking into account the measurements of both aerodynamic indices of nasal breathing and the calculation of energy characteristics [9,16,23], by which the olfactory sensitivity was determined (see Figure 2) [5,6].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a structural scheme of the method for the objective diagnosis of respiratory and olfactory disturbances was developed, taking into account the measurements of both aerodynamic indices of nasal breathing and the calculation of energy characteristics [9,16,23], by which the olfactory sensitivity was determined (see Figure 2) [5,6].…”
Section: Methodsmentioning
confidence: 99%
“…Since the analysis of recent researches and publications has shown that the method of rhinomatometry is the most objective functional method of modern otorhinolaryngology diagnosis, and the method of dynamic active posterior rhinomanometry (APR) is more reliable than the anterior active rhinomatometry, then it is proposed to add a definition to the standard APR method some parameters related to the function of the smell [16,23].…”
Section: Analysis Of Recent Research and Publicationsmentioning
confidence: 99%
“…Using custom made micro-manipulator, the electrode array was moved into the targeted brain area with the 5m step, until stable neural signal was recorded. Verification of a single unit activity was proved with wireless 8-channel system for extracellular electrophysiology [12,14,23] with simultaneous visualization of signal on oscilloscopes [6,26].…”
Section: Tip Of the 8-channel Electrode Array; (C) -8-channel Electromentioning
confidence: 99%